2015
DOI: 10.1371/journal.pone.0131476
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of PPP1R3D, a Protein Phosphatase 1 Targeting Subunit, Reveals a Binding Motif for 14-3-3 Proteins which Regulates its Glycogenic Properties

Abstract: Protein phosphatase 1 (PP1) is one of the major protein phosphatases in eukaryotic cells. It plays a key role in regulating glycogen synthesis, by dephosphorylating crucial enzymes involved in glycogen homeostasis such as glycogen synthase (GS) and glycogen phosphorylase (GP). To play this role, PP1 binds to specific glycogen targeting subunits that, on one hand recognize the substrates to be dephosphorylated and on the other hand recruit PP1 to glycogen particles. In this work we have analyzed the functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…4D). Since the R6-substrate-binding motif partially overlaps with the CBM domain (23), it is conceivable that glycogen competes with R6 binding to AMPK. Thus, our data suggest that low glycogen favors AMPKβ2/R6 interaction, whereas high glycogen content interferes with it.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4D). Since the R6-substrate-binding motif partially overlaps with the CBM domain (23), it is conceivable that glycogen competes with R6 binding to AMPK. Thus, our data suggest that low glycogen favors AMPKβ2/R6 interaction, whereas high glycogen content interferes with it.…”
Section: Discussionmentioning
confidence: 99%
“…R6 recruits PP1 phosphatase to its substrates (e.g., GS and GP) (23), thus playing a critical role in the regulation of glycogen metabolism. Most of the PP1-glycogen-targeting subunits exert their actions through binding to PP1 via a conserved Nterminal PP1-binding motif (RVXF), and interact with PP1-substrates via a conserved C-terminal substrate-binding (WXNXGNYX(L/I)) motif (23). We have recently shown that R6 utilizes this conserved region to bind to its glycogenic substrates GS and GP (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations